1995
DOI: 10.1007/bf00196928
|View full text |Cite
|
Sign up to set email alerts
|

Bulk delignification kinetics at selected vertical heights within jack pine plus trees

Abstract: Pulping kinetics of extractive-free wood from jack pine trees sampled from the Fort Frances, the Atikokan and the Thunder Bay districts of Ontario, Canada, were investigated. Wood samples were cooked at three different temperatures: 140 ~ 155 ~ and 170 ~ with a white liquor concentration of 32 g/L sodium hydroxide and 10.4 g/L sodium sulphide (25% sulphidity). The results indicated that the average activation energy for pulping of trees from the Fort Frances, the Atikokan and the Thunder Bay districts were 91.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Wong et al [9] also found a negligible difference in lignin solubilization between sapwood and heartwood in Pinus banksiana. However, differences between heartwood and sapwood occurred in the initial phase for 1608C and 1708C with a lower lignin solubilization in heartwood, for example, after 5 min at 1708C, 27% lignin was removed from heartwood and 37% from sapwood.…”
Section: Maritime Pine Pulping Yield and Delignification Kinetics 225mentioning
confidence: 91%
See 2 more Smart Citations
“…Wong et al [9] also found a negligible difference in lignin solubilization between sapwood and heartwood in Pinus banksiana. However, differences between heartwood and sapwood occurred in the initial phase for 1608C and 1708C with a lower lignin solubilization in heartwood, for example, after 5 min at 1708C, 27% lignin was removed from heartwood and 37% from sapwood.…”
Section: Maritime Pine Pulping Yield and Delignification Kinetics 225mentioning
confidence: 91%
“…The activation energies found in this study are in the range of reported values for other species, but only one reference could be found in the literature comparing heartwood and sapwood. Wong et al [9] reported values between 85.2 and 92.0 kJ . mol 21 for sapwood and between 89.6 and 90.6 kJ .…”
Section: Maritime Pine Pulping Yield and Delignification Kinetics 225mentioning
confidence: 97%
See 1 more Smart Citation